Gambir (Uncaria gambier) Processing and Marketing Techniques in Pesisir Selatan Regency, Indonesia - Saputra, Hendra; Azrifirwan (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aims to determine the Gambir processing technique in Pesisir Selatan Regency and the market potential associated with Uncaria Gambir. This study uses a qualitative research methodology that focuses on the socio-economic impact of the Gambir processing system in Pesisir Selatan, which shows the importance of Gambir as a primary livelihood for local communities. This area is characterized by unique Gambir processing techniques that contribute to ecological sustainability and financial viability for farmers. The study results show that Gambir processing is still carried out in traditional ways: harvesting, boiling, pressing, filtering, drying, molding, and drying. Furthermore, for marketing Gambir, it is done by farmers selling to collectors and then selling it to local exporters in Padang City. This study provides information on the important role of Gambir in the economic landscape of Pesisir Selatan. It provides a comprehensive view of processing techniques, market dynamics, and cultivation systems that are important for the sustainable development of this valuable natural resource. Contribution to Sustainable Development Goals (SDGs):SDG 1 – No PovertySDG 8 – Decent Work and Economic GrowthSDG 12 – Responsible Consumption and ProductionSDG 15 – Life on Land